Crosslinking capacity of tannic acid in plasticized chitosan films - Rivero, Sandra G. M. (2010)
Plasticized and unplasticized chitosan films with tannic acid addition were developed. The crosslinking capacity of tannic acid was studied by evaluating both the structural modification produced on chitosan films and its effect on physicochemical, barrier and mechanical properties. Likewise the changes of these properties during the storage were analyzed; formulations containing tannic acid increased 29% tensile strength whereas decreased 24% water vapor permeability. Film solubility decreased at 100 °C, confirming that exposure at high temperatures facilitates the crosslinking process. The presence of tannic acid and glycerol simultaneously showed a synergic effect on the studied properties, all of which presented intermediate behavior in relation to those determined with the addition of either acid or plasticizer. The effect of the storage was also relevant since the films evidenced their tendency to a more stable structure due to the reorganization toward an anhydrous conformation, as was demonstrated by X-ray diffraction and FTIR analysis.